S13 The microbiology of pleural infection, an approach based on 16s RRNA gene next generation sequencing. (12th November 2019) - Kanellakis, NI; Bedawi, E; Corcoran, JP; Gerry, S; Hallifax, R; Mercer, R; George, V; Dudina, A; Wrightson, JM; Asciak, R; Miller, R; Dobson, M; et al.
Abstract : Background: Pleural infection (PI) is a common and complicated disease, bearing a heavy healthcare burden worldwide. Definitive pathogen identification based on current methods occurs in only 40% of cases, mainly due to prior antibiotic administration and special bacterial nutritional culture requirements. To this end PI microbiology knowledge remains incomplete. Novel deep sequencing techniques could increase the rate of reliable pathogen identification and shed light on the complex polymicrobial patterns of PI. Aim: To investigate and further characterise the microbial nature of PI using next generation sequencing (NGS). Methods: Pleural fluid samples from the 'Pleural Infection Longitudinal Outcome Study' (PILOT, ISRCTN50236700, n=243) underwent bacterial DNA extraction followed by 16S rRNA NGS using Illumina MiSeq. Data were analysed with DADA2 and Phyloseq R packages. Results: Bacterial DNA from pleural fluid samples was successfully extracted and sequenced. NGS detected 391 diverse pathogens up to the genus level and analysis showed that PI is a polymicrobial disease. 131 (54%) samples had one pathogen with relative abundance over 50% and 89 (36%) samples had at least 3 pathogens with relative abundance over 10%. Streptococcus Pneumoniae was detected in 40 (16%) and Staphylococcus Aureus in 20 (8%) samples. Discussion: It is feasible to extract and sequence bacterial DNA from pleural fluid samples from patients with PI. 16S rRNA NGS is a robust method for investigating the total bacteriology of pleural fluid samples. Funding: National Institute for Health Research (NIHR) Oxford Biomedical Research Centre (BRC).